Analysis of indicators of intensity of P&D: Understanding the effects of the industrial structure and sectoral expenditures - Brigante, Paulo César [UNESP] (FapUNIFESP (SciELO), 2018)
This article examines the determinants of R&D business expenditures through an R&D intensity indicator defined by the ratio between R&D expenditures and industry value added. With the decomposition of its determinants, the objective of this article is to identify the extent to which Brazil’s distance in terms of technological efforts, measured by such indicator, in relation to the average of a set of selected countries, can be attributed to the effects of the industrial structure R&D expenditures made by the different technology groups that make up this industry.
Análise dos indicadores de intensidade de P&D: Entendendo os efeitos da estrutura industrial e dos gastos setoriais
Keywords: Business expenses in R&D; Innovation policies; Intensity R & D